Customer Relationship in Startups Companies: An Analysis of Publications in Marketing - Garzaro, Daniela Menezes; Varotto, Luís Fernando; Pedro, Samara Carvalho; Riccomini, Fernanda Edileuza (Future Studies Research Journal: Trends and Strategies, 2020)
Objective: To identify the current direction of research on relationship marketing in the business to consumer (B2C) modality at virtual environments (internet and cell phone applications), focusing on startups companies, highlighting the main constructs, the methods and the evolution of research over the recent years. Method: The research was developed by means of a systematic literature review, based on 62 articles selected from the Web of Science database, and a textual statistical analysis using the Iramuteq software. Originality/Relevance: This research is relevant for the field of relationship marketing due to the relative novelty of the theme, and the scarcity of studies in the area, with its originality in pointing out several gaps for future studies, especially in relation to brand, mobile apps and fintechs (technology finance). Results: The most prevalent themes in these studies were perceived quality, usefulness, ease of use and safety, and their relationship with customer satisfaction and loyalty. Theoretical/methodological contributions: There is a gap in the field of customer relationship at online environment, since few studies have been dealing with issues related to customer service and relationship quality, especially in the context of startups. Social contributions/to management: The deepening of the theme gives business managers from many segments, as well as relationship marketing professionals, the opportunity to get to know and reflect on the relationship between client and company and the means adopted as an interface for this relationship.